Oregano essential oil encapsulation following the complex coacervation method: Influence of temperature, ionic strength, and ph on the release kinetics in aqueous medium - Muneratto, Vítor Mathias [UNESP]; Gallo, Thais Cristina Benatti [UNESP]; Nicoletti, Vania Regina [UNESP] (FapUNIFESP (SciELO), 2021)
Oregano essential oil (OEO) exhibits antimicrobial and antioxidant properties. The bioactive compounds of OEO are volatile. Thus, encapsulation helps in protecting the activity of the compound when exposed to harmful conditions such as high (or low) temperature, light, and oxygen. Encapsulation also helps to improve the dispersibility of the compound in an aqueous medium, facilitating its application in formulated food products. We studied the release kinetics of OEO microencapsulated by gelatin/gum. Arabic complex coacervation was assessed, focusing on the influence of the physicochemical properties of the aqueous release medium (temperature (4, 25, and 30 ºC), ionic strength (0, 0.5, 1.0, and 1.5 M), and pH (3.8, 4.2, and 4.8)). Their capacity to act as release triggers was also investigated. High OEO release rates were recorded in the media with high ionic strengths (74% release in 5 h), high pH (78% release in 7 h), and low temperature (71% release in 7 h). In media at a temperature above 30 ºC and pH 3.8, the coacervated structure was disintegrated. A centered face experimental design (CFD) based on 17 samples was constructed, and an empirical model was developed to predict the maximum release conditions. The highest percentage of oil (reaching up to approximately 85%) is released over longer periods of time (7 h on an average) without damaging the integrity of the microcapsule. Peppas’ model showed the best fitting for all release profiles, with R² > 0.86 and relative average residual error < 6%, indicating the domain of Fickian diffusion during OEO release.
Encapsulação de óleo essencial de orégano pelo método de coacervação complexa: Influência da temperatura, força iônica e ph na cinética de liberação em meio aquoso
Keywords: Diffusion; Gelatin; Gum Arabic; Mass transfer; Microencapsulation